Quality of life, social support and cognitive impairment in heart failure patients without diagnosed dementia. Issue 2 (5th May 2015) - Gallagher, Robyn; Sullivan, Anne; Burke, Rhonda; Hales, Susan; Sharpe, Precilla; Tofler, Geoffrey
Abstract : Improving health‐related quality of life (HRQL) is an important goal for heart failure (HF) patients, and understanding the factors that influence HRQL is essential to this process. We investigated the influence of social support and cognitive impairment on HRQL in community dwelling HF patients ( n  = 104) without diagnosed dementia. Patients were aged mean 80.93 years (SD 11.01) and were classified as New York Heart Association Class 1/II (45%) or III/IV (53%). Age, social support and cognition had important independent effects. Younger people had the most negative effects of HF in all areas of HRQL: emotional ( B  = −0.32), physical ( B  = −0.44) and overall ( B  = −1). Well‐supported patients (general social support) had the least negative effect from HF on HRQL: emotional domain ( B  = −4.62) and overall ( B  = −11.72). Patients with normal cognition had more negative impact of HF on HRQL: physical domain ( B  = 5.51) and overall HRQL ( B  = 10.42). A clearer understanding of the relationships between age, social support and cognition and the effect on the impact of HF on HRQL is needed before interventions can be appropriately developed.